2D WC/WO3 Heterogeneous Hybrid for Photocatalytic Decomposition of Organic Compounds with Vis–NIR Light. (17th January 2018) - Wang, Song Ling; Zhu, Ye; Luo, Xin; Huang, Yun; Chai, Jianwei; Wong, Ten It; Xu, Guo Qin
Abstract: Developing catalysts to improve charge‐carrier transfer and separation is critical for efficient photocatalytic applications driven by low‐energy photons. van der Waals stacking of 2D materials has opened up opportunities to engineer heteromaterials for strong interlayer excitonic transition. However, fabrication of 2D heteromaterials with clean and seamless interfaces remains challenging. Here, a 2D tungsten carbide/tungsten trioxide (WC/WO3 ) heterogeneous hybrid in situ synthesized by a chemical engineering method has been reported. The hybrid comprises of layer‐by‐layer stacked WC and WO3 monolayers. The WC and specific interfacial interfaces between the WC and WO3 layers exhibit synergetic effects, promoting interfacial charge transfer and separation. Binderless WC performing platinum‐like behavior works as a potential substitute for noble metals and accelerates multielectron oxygen reduction, consequently speeding up the photocatalytic decomposition of organic compounds over the WO3 catalyst. The specific interfacial interaction between WC and WO3 layers potentially improves interfacial charge transfer from conduction band of WO3 to WC. In the absence of noble metals, the WC/WO3 hybrid as a catalyst exhibits distinct decomposition of organic compounds with vis–NIR light (λ = 400–800 nm). This finding provides a cost‐effective approach to capture low‐energy photons in environmental remediation applications. Abstract : 2D WC/WO3 heterogeneous hybrid is synthesized via an in situ chemical engineering method. The hybrid comprising of layer‐by‐layer stacked WC and WO3 exhibits distinct charge transfer and separation. In the absence of noble metals, the WC/WO3 hybrid exhibits excellent oxidative decomposition of organic compounds driven by the low‐energy photons (vis–NIR light).